ANALISIS TINGKAT KEPUASAN MASYARAKAT TERHADAP KINERJA PELAYANAN PUBLIK KANTOR KECAMATAN RONGKOP KABUPATEN GUNUNGKIDUL - Luthfi Ferdinand Ahmad; Ary Sutrischastini (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2015)
This paper aims to determine the level of societys satisfaction with the performance of public services in Rongkop OfficeDistrict. Data is obtained by using a questionnaire. Questionnaire of Community Satisfaction Index (HPI) to the performance of services is based on the decision Men.PAN Number: KEP / 25M.PAN / 2/2004. Respondentsare 150 people. The result of research are: (1) Elements of serviceincluded in the excellent category A is the security environment. (2) The element of services that fall into category B are the terms of service, service personnel clarity, speed of service, courtesy and friendliness of the clerk, and comfortable environment. (3) The element of services that fall into the category of less good C are the sub-district service procedures, responsibilities of service personnel, the ability of service personnel, service personnel discipline, justice get service, the reasonableness of the cost of the service, the service cost certainty, and certainty of the service schedule. (4) Overall Community Satisfaction Index (HPI) on the performance of public services in the Rongkop Gunungkidul District is in category B, with the value of 69.7.